Optimization of quadratures on classes of functions given by differential operators with Real Spectra - Babenko, V. V.; Rudenko, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We study the problem of optimization of quadrature formulas for broad classes of periodic functions defined in terms of differential operators with real spectra. We analyze quadrature formulas containing values of functions and values of the images of functions under the action of some differential operators. The rectangular formula is proved to be optimal.